2014
DOI: 10.1017/s1742170514000349
|View full text |Cite
|
Sign up to set email alerts
|

Forage potential of six leguminous green manures and effect of grazing on following grain crops

Abstract: There is a need to design intensive cropping systems that can reap multiple benefits from annual forages including animal feed, soil fertility and weed control. Considering pea/oat (Pisum sativumcv. 40–10/Avena sativacv. Legget) as a standard green manure, this study investigated the productivity, weed competitiveness, utilization and nitrogen (N) benefit from grazed and ungrazed green manures to spring wheat (Triticum aestivumcv. Waskada) and fall rye (Secale cerealecv. Hazlet). A set of 3-year experiments wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 61 publications
5
15
0
Order By: Relevance
“…It should be emphasized that the higher-N input to the soil-plant system, derived from the biological fixation carried out on legumes, may have contributed to improvements of soybean yield, as it is a source that is gradually released through mineralization. This result corroborates those by Cicek et al (2014), who showed a wheat yield increase in the ICLS, with the intercropping of two species of forage legumes, and accounted this result to the N that was slowly added via legume residues. Moreover, cultivations of distinct species cooperate in the maintenance of nutrient balance in the soil and in the improvement of their fertility, reflecting in better yields of the successive crop.…”
Section: Resultssupporting
confidence: 92%
“…It should be emphasized that the higher-N input to the soil-plant system, derived from the biological fixation carried out on legumes, may have contributed to improvements of soybean yield, as it is a source that is gradually released through mineralization. This result corroborates those by Cicek et al (2014), who showed a wheat yield increase in the ICLS, with the intercropping of two species of forage legumes, and accounted this result to the N that was slowly added via legume residues. Moreover, cultivations of distinct species cooperate in the maintenance of nutrient balance in the soil and in the improvement of their fertility, reflecting in better yields of the successive crop.…”
Section: Resultssupporting
confidence: 92%
“…Somewhat more recently, Gül et al (2008) found that silage maize did not respond to the application of more than 12 kg N da -1 following the cultivation of Hungarian vetch instead of leaving the land fallow. In other studies, forage peas have also positively affected cash crop yields when used as cover crops (Bahl et al, 2000;Skoufogianni et al, 2013;Marsh, 2014;Cicek et al, 2014;Liebman et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…Due to the web of relationships within ecosystems, manipulating one process may cause changes throughout the system, possibly introducing new risks of unintended consequences and requiring complementary changes to manage these risks. For example, grazing a legume-based green manure cover crop can increase total productivity and profitability by generating income from livestock products while preserving the nitrogen credit to following crops through accelerated decomposition of green manure plant residues (Cicek et al, 2015a; Thiessen Martens and Entz, 2011). But this accelerated decomposition rate can increase fall soil nitrate concentration, potentially posing a risk of leaching (Cicek et al, 2014).…”
Section: Approaches To Restoring Prairie Ecosystem Functioningmentioning
confidence: 99%